2012
DOI: 10.1016/j.ejvs.2012.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Disease Specific Biomarkers of Abdominal Aortic Aneurysms Detected by Surface Enhanced Laser Desorption Ionization Time of Flight Mass Spectrometry

Abstract: This study discovered a signature plasma protein profile for patients with AAA and demonstrated that mass spectrometric based research for disease specific biomarker of AAA is feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…If the oral cancer was found at early stages of development, it has an 80 to 90% survival rate. Unfortunately, most of these cancers are hard to discover in the early stages because of a lack of public awareness and screening method, which would generally result in a poor prognosis and a low survival rate 4 .…”
mentioning
confidence: 99%
“…If the oral cancer was found at early stages of development, it has an 80 to 90% survival rate. Unfortunately, most of these cancers are hard to discover in the early stages because of a lack of public awareness and screening method, which would generally result in a poor prognosis and a low survival rate 4 .…”
mentioning
confidence: 99%
“…Two protease inhibitors, α-1-antitrypsin (SERPINA1) and kallistatin (SERPINA4), have been newly identified as potential biomarkers [ 23 27 ]. Furthermore, PRDX1, CAT and HP are involved in redox regulation, or are antioxidant proteins, and were detected as possible biomarker candidates from the red blood cell membrane, cultured macrophages, and the serum or plasma of AAA patients [ 24 , 26 , 28 31 ].…”
Section: Abdominal Aortic Aneurysm and Biomarker Search Using Blood Smentioning
confidence: 99%
“…The list of these proteins is reported in Supplementary Table 3. Fibrinogen gamma-chain FIBG_HUMAN [28,32,34] To determine the importance of inflammatory response in causing hemodynamic instability in the early postoperative period after AAA surgery, we performed a study to define the plasma proteomic changes after AAA repair [34]. We observed an enhanced thrombin expression at 6 h after declamping.…”
Section: Go:0006955 Immune Responsementioning
confidence: 99%
“…They identified in AAA subjects four serum proteins that showed altered expression profile and that could be specifically linked to AAA pathology. A recent research, conducted by Ehsan et al [32], showed that surface enhanced laser desorption ionization time of flight (SELDI-TOF) can be used to study the plasma protein expression of AAA. They identified a plasma protein profile that could classify patients from a mixed population group.…”
Section: Go:0006955 Immune Responsementioning
confidence: 99%
See 1 more Smart Citation